THE IDENTIFICATION OF CHANGES OF SIGNIFICANT NECESSITIES, THAT ARE TYPICAL FOR THE PERSONALITY OF THE COMBATANT IN THE COURSE OF THE REHABILITATION PERIOD - Karachynskyi, O. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2020)
The article is dedicated to the research of identifying the changes of significant necessities, that are typical for the personality of combatants in the course of the rehabilitation period. In order to identify significant necessities, that are typical for the personality of combatants the method of color selection has been used. It is referred to the necessities that are determined by main colors: the necessity of satisfaction and affection, the necessity of self-empowerment, the necessity of achievement, obtainment, power; the necessity of social activity and emotional engagement. When interpreting the results, the orientation was aimed at the first, second and seventh and eight positions, though we had the intention to receive the information concerning the main way of action and its purpose, the one that the researcher is planning to reach as well as his suppressed necessities. At the initial stage of research within the experimental group (EG) the main necessities and tendencies were focused on activity, the emotional engagement, and simultaneously the necessity to lose the actual reality. At the final stage of research prominent remains the necessity to stay active, and emotionally engaged there’s no longer a necessity to lose the actual reality. Prior becomes the need to fortify ones’ position. The main necessities of the control group were: the need to sense intense affiliation, the tendency to achieve external protection and emotional comfort; the need to be emotionally engaged, active, the tendency to be passive. When comparing the fixed stages of the experiment we could obviously claim that the prior necessities of control groups under research have practically not changed. However, at the final stages of research there turned out to be features of harmonizing the personality.